Guyana - Investment Climate Assessment : Volume 1. Main Findings and Policy Recommendations - World Bank (Washington, DC, 2012)
This document presents the main findings of the Guyana Investment Climate Survey (ICS) conducted between November 2004 and March 2005. The ICA report provides an evaluation of different aspects of the environment of doing business in Guyana. It covers governance-related obstacles, labor and technology issues, the financial sector, and infrastructure. The ICA is based on the results of the World Bank Guyana Investment Climate Survey (ICS), as well as other sources of information, including an opinion survey of Guyanese commercial bank managers, and interviews with Guyanese entrepreneurs and government leaders. The findings of the survey, combined with relevant information from other sources, provide a practical basis for identifying the most important areas for reform aimed at improving the investment climate.